Redaksi dan Daftar Isi, Jurnal Arsitekta Vol. 03 No. 01, Mei 2021 - ojsadmin TAU (Program Studi Arsitektur Universitas Tanri Abeng, 2021)
Redaksi dan Daftar Isi, Jurnal Arsitekta Vol. 03 No. 01, Mei 2021